Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.plantsci.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Seed maturation: Simplification of control networks in plants

Abstract: Networks controlling developmental or metabolic processes in plants are often complex as a consequence of the duplication and specialisation of the regulatory genes as well as the numerous levels of transcriptional and post-transcriptional controls added during evolution. Networks serve to accommodate multicellular complexity and increase robustness to environmental changes. Mathematical simplification by regrouping genes or pathways in a limited number of hubs has facilitated the construction of models for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 92 publications
3
36
0
Order By: Relevance
“…Mutations in ABI3 and FUS3 lead to desiccation intolerance, mutations in FUS3 lead to a viviparous phenotype and mutations in ABI3, FUS3 and LEC2 result in a decrease in protein storage and lipid reserves in the seeds but an increase in starch. Homologues of AFL genes seem to be present in the genomes of all seed plants sequenced to date and in some moss and algae (Devic and Roscoe 2016), and it has been suggested that their function is conserved in all seed plants (Agarwal et al 2011;Schallau et al 2008;Sreenivasulu and Wobus 2013). miRNAs act by repressing the positive regulators of the seed maturation program during early embryogenesis, as evidenced by the up-regulation of FUS3, LEC2, , and several MYBs and bZIPs in the dcl1-15 mutant (Willmann et al 2011).…”
Section: Transition To Maturation and Accumulation Of Storage Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in ABI3 and FUS3 lead to desiccation intolerance, mutations in FUS3 lead to a viviparous phenotype and mutations in ABI3, FUS3 and LEC2 result in a decrease in protein storage and lipid reserves in the seeds but an increase in starch. Homologues of AFL genes seem to be present in the genomes of all seed plants sequenced to date and in some moss and algae (Devic and Roscoe 2016), and it has been suggested that their function is conserved in all seed plants (Agarwal et al 2011;Schallau et al 2008;Sreenivasulu and Wobus 2013). miRNAs act by repressing the positive regulators of the seed maturation program during early embryogenesis, as evidenced by the up-regulation of FUS3, LEC2, , and several MYBs and bZIPs in the dcl1-15 mutant (Willmann et al 2011).…”
Section: Transition To Maturation and Accumulation Of Storage Productsmentioning
confidence: 99%
“…In 2010, the web-based information portal RIMAS (Regulatory Interaction Maps of Arabidopsis Seed Development, http://rimas.ipk-gatersleben.de / Junker et al 2010) provided an overview of the LEC1/AFL-B3 network of TFs during Arabidopsis embryo and seed maturation, which reflects the interactions of several regulatory mechanisms including gene promoters, hormonal pathways and epigenetics. More recently, based on current information, Devic and Roscoe (2016) proposed a model for regulation of the AFL network during embryo development and transition to vegetative growth in Arabidopsis that reflects the involvement of miRNAs. In this model, and in addition to miR156, miRNA166 is also relevant since one of its target genes, PHB, is a direct activator of LEC2 (Tang et al 2012), revealing a regulatory module consisting of a miRNA, its target genes (PHB and PHV), and a direct target of PHB (LEC2).…”
Section: Micrornas As Components Of Gene Regulatory Network In Seed mentioning
confidence: 99%
See 1 more Smart Citation
“…The network for AFL master regulators, ABSCISIC ACID INSENSITIVE3 (ABI3), FUSCA3 (FUS3), LEAFY COTYLEDON1 (LEC1), and LEC2 have been studied with the aim of controlling the biosynthesis of Arabidopsis seed oil (North et al, 2010; Roscoe et al, 2015; Devic and Roscoe, 2016). This network can regulate the expression of genes encoding enzymes that synthesize the storage lipids and protein reserves in seeds.…”
Section: Introductionmentioning
confidence: 99%
“…LEC2 may regulate fatty acid biosynthesis genes through direct regulation of WRI1 (Baud et al, 2007). Although ABI3 is not known to directly regulate the expression of WRI1 , it is known that ABI3, FUS3, LEC1, and LEC2 regulate the downstream genes through synergistic interactions with each other during seed maturation (Devic and Roscoe, 2016). The WRI1 gene was first identified in an Arabidopsis mutant exhibiting wrinkled seed morphology; it encodes an AP2/EREBP type transcription factor (Focks and Benning, 1998).…”
Section: Introductionmentioning
confidence: 99%